Intra-Species and Inter-Kingdom Signaling of Legionella pneumophila - Hochstrasser, Ramon; Hilbi, Hubert (Frontiers in Microbiology, 2017)
The ubiquitous Gram-negative bacterium Legionella pneumophila parasitizes environmental amoebae and, upon inhalation, replicates in alveolar macrophages, thus causing a life-threatening pneumonia called “Legionnaires’ disease”. The opportunistic pathogen employs a bi-phasic life cycle, alternating between a replicative, non-virulent phase and a stationary, transmissive/virulent phase. L. pneumophila employs the Lqs (Legionella quorum sensing) system as a major regulator of the growth phase switch. The Lqs system comprises the autoinducer synthase LqsA, the homologous sensor kinases LqsS and LqsT, as well as a prototypic response regulator termed LqsR. These components produce, detect and respond to the α-hydroxyketone signaling molecule LAI-1 (Legionella autoinducer-1, 3-hydroxypentadecane-4-one). LAI-1-mediated signal transduction through the sensor kinases converges on LqsR, which dimerizes upon phosphorylation. The Lqs system regulates the bacterial growth phase switch, pathogen-host cell interactions, motility, natural competence, filament production and expression of a chromosomal “fitness island”. Yet, LAI-1 not only mediates bacterial intra-species signaling, but also modulates the motility of eukaryotic cells through the small GTPase Cdc42 and thus promotes inter-kingdom signaling. Taken together, the low molecular weight compound LAI-1 produced by L. pneumophila and sensed by the bacteria as well as by eukaryotic cells plays a major role in pathogen-host cell interactions.